Early De-resuscitation Strategy using Diuretics Targeting Low Central Venous Pressure in the Management of Septic Shock with Acute Kidney Injury - Gabriana, Jessica; George, Yohannes W.H.; Purwowiyoto, Sidhi Laksono (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Septic shock remains a critical condition associated with high morbidity and mortality rates, particularly when complicated by Acute Kidney Injury (AKI). Traditional management strategies have predominantly emphasized fluid resuscitation to restore hemodynamic stability; however, the adverse effects of fluid overload are most pronounced in situations such as septic shock, which predisposes patients to acquired AKI. This case report presents an early de-resuscitation strategy using diuretics to target low central venous pressure (CVP) in a 58-year-old male with Urosepsis-associated AKI. The initial treatment included fluid loading and antibiotics, but his condition worsened, leading to ICU admission. A central venous catheter was placed, and a furosemide infusion was started due to positive fluid balance and high CVP. Over the next few days, the patient's condition improved significantly, with reduced ventilator and vasopressor support and improved renal function. The success of this strategy underscores the importance of re-evaluating fluid resuscitation practices and incorporating de-resuscitation as a key component of patient care.